Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/clc.22865
|View full text |Cite
|
Sign up to set email alerts
|

Effect of type D personality on smoking status and their combined impact on outcome after acute myocardial infarction

Abstract: Type D personality and smoking status increase the risk of cardiac events. An emotionally stressed personality and persistence of smoking after the first cardiac event, and mostly their mutual influence, indicate a population at high cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…In another study performed with a different disease group where the effect of type D personality on smoking status after myocardial infarction was examined, patients without type D personality were found to have greater rates of quitting smoking compared to patients with type D personality. 29 Type D personality is characterized by a predilection to increased negative affect and the suppression of such affect in social environments however, it is still not clear which mechanisms are related to negative clinical outcomes. These mechanisms include both physiological and behavioral factors and the most prominent behavioral connection may be the failure to modify risk factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In another study performed with a different disease group where the effect of type D personality on smoking status after myocardial infarction was examined, patients without type D personality were found to have greater rates of quitting smoking compared to patients with type D personality. 29 Type D personality is characterized by a predilection to increased negative affect and the suppression of such affect in social environments however, it is still not clear which mechanisms are related to negative clinical outcomes. These mechanisms include both physiological and behavioral factors and the most prominent behavioral connection may be the failure to modify risk factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the study of Garcia et al, which revealed that respondents with type D personality who smoked had a high blood pressure systole and thus had poor lipid profile examination results, especially concerning HDL (Garcia-retamero, Petrova, & Ram, 2016). An increase in lipids is caused by the lifestyle of patients with type D personality who are less healthy, such as a lack of exercise, smoking and not following the recommended diet (Imbalzano et al, 2018). In addition, type D patients often lack social support, which can indirectly contribute to the failure to adopt a healthy lifestyle and lipid control.…”
Section: Discussionmentioning
confidence: 99%
“…The Multiple Risk Factor Intervention Trial revealed that smoking cessation is the strongest predictor of lower rates of coronary artery disease as compared with other changes in risk factors, such as cholesterol and blood pressure lowering interventions in high-risk men [12]. However, smoking cessation is a diffi cult process which is infl uenced by many factors such as educational level, personality, psychosocial circumstances, work satisfaction, poor family income and the presence of a partner [13][14][15]. The long duration and high intensity of pre-STEMI smoking are also associated with smoking cessation rates in STEMI patients [7,16].…”
Section: Methodsmentioning
confidence: 99%